Teaching Explanation Difficulties in Islamic University from the lecturers Point of View (Journal Of Educational and Psychological Researches, 2010)
This study is about awareness of teaching explanation difficulties in the Islamic university from the lecturers point of view. It discussed the difficulties and the traditional teaching methods of explanation. The study concentrated on teaching Islamic studies in general and teaching explanation in specific and set difficulties so as to be treated.             The study is of three chapters, the first contains the difficulties in several aspects like the educational goals, text contents, teaching methods and styles, students, educational techniques, educational aids and evaluation, it addition to the lecturers of Islamic university colleges in 2009-2010, the difficulties were set and teaching explanation in linguistic and terminology and procedurally with identifying the term Islamic university.            The second chapter includes a presentation to three previous studies on this subject and how benefit taken from them. The third one has the research methodology and its procedures as it depended on the descriptive method to have reliable results.             The researcher her set the study community and its sample which reached 30 lecturer from the different college of the university like ; college of religion bases, college of education for women, college of education in tarmiya, college of Islamic studies, and college of arts.             In this research, the sample was determined by a comprehensive study and the community was identified as a sample. Questionnaire was used as a research method relying on likert quinary criterion.            The difficulties were proved to be true by applying person which reached (0.79) and the questionnaire contained 63 difficulty and the results were got by the probable medium and percentage weight.             In the forth chapter there is the results with discussion to each which were 38 item. The difficulties were from the sample point of view that includes 63 item because it got more than (3) probable medium and more than 60 y.            Percentage weight, In addition to some suggestion for further studies.